2019
DOI: 10.3892/etm.2019.8039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ulinastatin combined with mild therapeutic hypothermia on intestinal barrier dysfunction following cardiopulmonary resuscitation in rats

Abstract: The aim of the present study was to investigate the effect of ulinastatin (UTI) alone or combined with mild therapeutic hypothermia (MTH) on intestinal barrier dysfunction following cardiopulmonary resuscitation (CPR) in rats. A total of 25 adult male Sprague-Dawley rats were randomly organized into five groups: Sham; control; UTI; MTH; and the combined group. The latter four groups were induced with the asphyxiated cardiac arrest rat model and treated with different interventions. After 6 h of treatment, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a clinical setting, intestinal dysfunction is of subordinate relevance next to cardiac, pulmonary, and cerebral failure and their importance in ECMO therapy. In regard to therapeutic measures, medication with ulinastatin is currently a topic of interest in ischemia-induced intestinal barrier dysfunction [ 40 ]. Ulinastatin is a serine protease inhibitor that has anti-inflammatory characteristics and has been widely used as a treatment for patients with inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, intestinal dysfunction is of subordinate relevance next to cardiac, pulmonary, and cerebral failure and their importance in ECMO therapy. In regard to therapeutic measures, medication with ulinastatin is currently a topic of interest in ischemia-induced intestinal barrier dysfunction [ 40 ]. Ulinastatin is a serine protease inhibitor that has anti-inflammatory characteristics and has been widely used as a treatment for patients with inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…And the levels of MDA and SOD in tissues were also determined in our study. MDA, a substance produced by reactive oxygen after degrading polyunsaturated lipids and may lead to intracellular toxic stress, is an indicator of oxidative stress, while SOD is a pivotal antioxidant in cells [13]. With a smaller elevation of MDA and larger elevation of SOD, CRRT cooling may alleviate the renal and intestinal injury by suppressing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hasslacher et al [11] showed that TH had a protective effect against the development and recovery of AKI, accompanied by lower levels of creatinine (Cr) and cystatin C. With regard to the role of TH on intestinal injury, a study showed TH alone or in the combination with sevo urane could affect small intestinal protein expression and activity, and the proteins might be involved in intestinal I/R injury following resuscitation [12]. Another study showed that ulinastatin combined with TH might exert a protective effect in the small intestinal mucosa by decreasing oxidative stress in a rat model [13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstratedthat24hr of TH after CPR was associated with a delayed improvement in renal function [10].Hasslacher et al [11] showed that TH had a protective effect against the development and recovery of AKI, accompanied by lower levels of creatinine (Cr) and cystatin C. With regard to the role of TH on intestinal injury, a study showed TH alone or in the combination with sevo urane could affect small intestinal protein expression and activity, and the proteins might be involved in intestinal I/R injury following resuscitation [12]. Another study showed that ulinastatincombined with TH mightexert a protective effect in the small intestinal mucosa by decreasing oxidative stress in a rat model [13].…”
Section: Introductionmentioning
confidence: 99%